MINAT MASYARAKAT DUSUN SEGURI MERAH AIR TERHADAP MUSIK TRADISIONAL GENDANG SEDAYUNG SUKU DAYAK KETUNGAU SESAEK - Arsen, Petrus; Mering, Aloysious; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is motivated by presence traditional music Gendang Sedayung in Seguri Merah Air Hamlet Sekadau Regency. This study is about the interest of Seguri Merah Air Hamlet Cociety against traditional music Gendang Sedayung Dayak Ketungau Sesaek Tribe. The study was conducted in Seguri Merah Air Hamlet, Village of Peniti, District of Sekadau Hilir, Sekadau Regency. This research uses descriptive-qualitative research. The obtained data through this research is the fact about the efforts of Seguri Merah Air Hamlet Cociety in maintaining the interest of Seguri Merah Air Hamlet cociety against Music Gendang Sedayung, the pattern wasp of Music Gendang Sedayung Dayak Ketungau Sesaek Tribe, and the implementation of Music Gendang Sedayung in the school. On the strength of data analysis, it can be summarized as follows; (1) The interest of Seguri Merah Air Hamlet Cociety against Music Gendang Sedayung is "high". (2) The pattern wasp of Music Gendang Sedayung Dayak Ketungau Sesaek Tribe is "A-A". (3) Music Gendang Sedayung can be implemented in schools using the curriculum in 2013.Keywords : Interest, Music, Gendang Sedayung.